EFEKTIVITAS PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI VIRUS DI SMAN 01 KUBU, KALIMANTAN BARAT - Sari, Wita Kusuma; Rahayu, Hanum Mukti; Sunandar, Ari (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Animated video media can make students interested in learning. The objectives of this research are, 1) To determine the differences in learning outcomes and learning activities of class class X student activities between classes that use animated video media and classes that use powerpoint media. The research sample was all students in class X Mia 1 and Mia 2. Data were collected using the test method in the form of multiple-choice questions and observation sheets. Data analysis uses quantitative descriptive analysis techniques. Based on the research results, it was obtained using the t-test there was a significant difference in student activity in class of 0.048, and in learning outcomes there was a significant difference of 0.000. Based on the Effect Size results, activity results were obtained at 0.51 and student learning outcomes at 0.50, including in the medium category.